Mobile Phones Reduce the Penetration Ability of Human Spermatozoa And Increase the Percentage of Swollen Sperm in the Seminal Fluid of Humans.: Life Sciences -Environmental science - Asit Kumar, Dr.; Dubey, Late A.K. (International Journal of Life Science and Pharma Research, 2023)
Generally, people hold mobile phones in the pocket of their pants, especially near the testes, and for that reason, the possible effects of mobile on reproductive health have become a matter of serious concern. The biological responses of such exposure caused various adverse effects on almost all biological systems. So, the present research has been proposed to study the biological responses of different duration of mobile phone usage on certain sperm functional parameters like penetration ability of spermatozoa and percentage of swollen sperm through an artificial medium (polyacrylamide) and Hypo Osmotic Swelling Test, respectively. For this, semen was collected from 65 men who used a mobile phone (SAR value 2.0 W/Kg averaged over 10gram tissue) at least 3 hours a week and kept mobile in their waist pocket. Semen was also collected from 22 men who never used mobile phones and were regarded as control. Their semen is analyzed according to the method given in the WHO laboratory manual for examining human semen, 5th edition, (2010). The results showed a highly significant (p<0.001) decreased spermatozoa penetration ability and a highly significant increased (p<0.001) level of percentage swollen spermatozoa in hypoosmotic swelling test (HOST) in human subjects using mobile phones in the last 01-05 years, 06-09 years and more than 10 years of duration in comparison to non-users human subjects. Evidence from current studies suggests the potentially harmful effects of mobile phones on certain sperm functional parameters and makes the seminal fluid infertile. A further standardized study is needed to assess the risk of mobile phone use on the reproductive system.